A simple in vitro method to study interactions between soil insects, entomopathogenic fungi, and plant extracts. Issue 3 (21st May 2017) - Eckard, Sonja; Bacher, Sven; Enkerli, Jürg; Grabenweger, Giselher
Abstract: A combined application of a biological control agent, such as an entomopathogenic fungus (EPF), with other means of pest control may lead to enhanced or more reliable efficacy of the biocontrol agent. Ideally, the combined components would interact synergistically, yielding significantly higher mortality of the target pest. The mode of such interactions is often unclear and particularly difficult to elucidate for soil‐dwelling pests. Here, an efficient image analysis protocol was developed to study behavioural responses of soil‐dwelling insects to application of control measures in two‐dimensional terraria. The interactions between the EPF Metarhizium brunneum Petch (Hypocreales), a supposedly repellent extract of garlic, Allium sativum L. (Amaryllidaceae), and wireworms, Agriotes obscurus (L.) (Coleoptera: Elateridae), as target hosts were investigated. Tunnelling activity and mortality of wireworms were studied under choice and no‐choice situations of various combinations of the control agents. A treatment with Metarhizium spores resulted in wireworm mortalities of about 80%. Contrary to expectations, a combination of the EPF with the garlic extract did not increase, but slightly decrease wireworm mortality. The data gained from the image analysis revealed that the tunnelling activity of wireworms was clearly reduced in the presence of garlic, which, together with a reduced germination rate of spores, is a possible explanation for the antagonism detected in the combined treatment. The methodological approach developed here can be used to study the interactions among control agents and soil insects over several days and weeks.